PENGEMBANGAN MEDIA PETA SEJARAH BERBASIS MACROMEDIA FLASH SEBAGAISARANA SISWA BELAJAR MANDIRI - Kurniawan, Imam Satria; Suryani, Nunuk; Djono, D. (Sebelas Maret University (UNS), 2018)
Research development aims to: ( 1 ) described on use media teaching history in high school land 1 muara sugihan; ( 2 ) described development media map history; ( 3 ) test the effective of media as a means of students independent study. Research conducted is research development research and development in a ADDIE was of molenda who mencangkup: ( 1 ) analysis of necessity; ( 2 ) make a medium; ( 3 ) the development of design got a product that will validated by the , and in ujicobakan one by one , small group , and broad , ( 4 ) the implementation of media at class experimentation; ( 5 ) test the effectiveness of . Conclusion ( 1 ) learning not use media of learning; ( 2 the media map history get the average score 40 by the matter and 31.5 for the judgment of media so dikatagorikan good , pilot one by one , small group , broad showed the media can used as a means of students independent study .( 3 ) the effectiveness of media as a means of independent study from the test t obtained the economic situation of significance 0,005<0,025 show H0 rejected which means that there is a difference in an increase in independent study students experimentation and control.